Divorce Mediation at Religious Courts in Pasangkayu during the Covid-19 Pandemic: Socio-Juridical Analysis - Gasim Yamani; Nazil Fahmi; Muhammad Akbar (INTERNATIONAL JOURNAL OF CONTEMPORARY ISLAMIC LAW AND SOCIETY, 2022)
This article describes the application of divorce mediation and explains the factors that influence mediation practices during the Covid-19 pandemic at the Religious Courts in Pasangkayu. As part of the alternative settlement of disputed cases, mediation has changed its implementation, including in the practice of law in religious courts. This study uses a socio-juridical approach to examine qualitative data obtained from field research through observation, in-depth interviews, and documentation. This study presents three conclusions. First, divorce mediation includes pre-mediation, which is carried out privately, and its implementation is based on the situation. Second, several enabling and inhibiting factors influence the practice of meditation. Third, from a socio-juridical perspective, mediation is a construction guided by the principle of agreement carried out through deliberation and consultation regarding disputes. In addition to adhering to a positive legal system, mediation in religious courts in Indonesia attaches to the Regulation of the Minister of Religious Affairs Number 1 of 2006 and the process of judging (tahkim) procedure in Islamic law. The influence of local customs and culture on the implementation of mediation in religious courts is not by the objectives of Islamic law and positive law, which is oriented toward the peaceful settlement of disputes and good faith.